TPD52L2 Is a Prognostic Biomarker and Correlated With Immune Infiltration in Lung Adenocarcinoma - Zhong, Anyuan; Chen, Ting; Zhou, Tong; Zhang, Zengli; Shi, Minhua (Frontiers in Pharmacology, 2021)
Tumor protein D52-like 2 (TPD52L2) belongs to the members of the TPD52 family. TPD52L2 was reported to regulate proliferation and apoptosis in cancer cells. However, its role in lung adenocarcinoma (LUAD) was uncertain. We evaluated the expression, methylation, copy number alteration, and prognostic significance of TPD52L2 using RNA-seq data from The Cancer Genome Atlas (TCGA). Enrichment analysis of TPD52L2 was conducted using the R package “clusterProfiler”. We further assessed the association between TPD52L2 and immune cell infiltration level, immunosuppressive genes, and tumor mutation burden (TMB). The difference of gene mutant frequency in high and low TPD52L2 groups was also analyzed. Results showed that TPD52L2 was over-expressed and predicted worse survival status in LUAD. We also found that TPD52L2 expression was positively associated with the infiltration levels of immunosuppressive cells, such as regulatory T cells (Tregs), and tumor-associated macrophages (TAMs) and negatively correlated with immune killer cells, such as CD8+ T and NK cells in pan-cancer, including LUAD. In addition, TPD52L2 expression was associated with immunosuppressive genes and TMB. High expression of TPD52L2 was with more mutant frequency of TP53. In summary, our results show that TPD52L2 is an oncogene and a potential prognostic biomarker in LUAD. High TPD52L2 expression is a possible indicator of immune infiltration and associated with tumor immunosuppressive status in LUAD.